NHX-Type Na+/H+ Antiporter Gene Expression Under Different Salt Levels and Allelic Diversity of HvNHX in Wild and Cultivated Barleys - Jabeen, Zahra; Irshad, Faiza; Hussain, Nazim; Han, Yong; Zhang, Guoping (Frontiers in Genetics, 2022)
Salinity tolerance is a multi-faceted trait attributed to various mechanisms. Wild barley is highly specialized to grow under severe environmental conditions of Tibet and is well-known for its diverse germplasm with high tolerance to abiotic stresses. The present study focused on determining the expression profile of HvNHX gene isoforms in 36 wild and two cultivated barleys under salt stress. Our findings revealed that expression of HvNHX1 and HvNHX3 in leaves and roots of XZ16 and CM72 genotypes was up regulated at all times as compared with sensitive ones. The HvNHX2 and HvNHX4 isoforms were also induced by salt stress, although not to the same extent as HvNHX1 and HvNHX3. Gene expression analysis revealed that HvNHX1 and HvNHX3 are the candidate genes that could have the function of regulators of ions by sequestration of Na+ in the vacuole. HvNHX1 and HvNHX3 showed a wide range of sequence variation in an amplicon, identified via single nucleotide polymorphisms (SNPs). Evaluation of the sequencing data of 38 barley genotypes including Tibetan wild and cultivated varieties showed polymorphisms including SNPs, small insertion and deletion (INDELs) sites in the targeted genes HvNHX1 and HvNHX3. Comprehensive analysis of the results revealed that Tibetan wild barley has distinctive alleles of HvNHX1 and HvNHX3 which confer tolerance to salinity. Furthermore, less sodium accumulation was observed in the root of XZ16 as compared to the other genotypes as visualized by CoroNa-Green, a sodium-specific fluorophore. XZ16 is the tolerant genotype, showing the least reduction of roots and leaves dry weight under moderate (150 mM) and severe (300 mM) NaCl stress. Evaluation of genetic variation and identification of salt tolerance mechanism in wild barley could be promoting approaches to unravel the novel alleles involved in salinity tolerance.